2019
DOI: 10.1186/s12913-019-4694-9
|View full text |Cite
|
Sign up to set email alerts
|

Small is beautiful? Explaining resident satisfaction in Swedish nursing home care

Abstract: BackgroundResident satisfaction is an important aspect of nursing home quality. Despite this, few studies have systematically investigated what aspects of nursing home care are most strongly associated with satisfaction. In Sweden, a large number of processual and structural measures are collected to describe the quality of nursing home care, though the impact of these measures on outcomes including resident satisfaction is poorly understood.MethodsA cross-sectional analysis of data collected in two nationally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 50 publications
0
8
1
Order By: Relevance
“…To enhance the institutional satisfaction of hypertension patients within elderly caring SOs, we suggest that elderly caring SOs should improve their environment and service quality while also expanding social capital into the elderly care sector to provide targeted elderly care services. The findings of previous study indicated that nursing home residents are more satisfied in smaller nursing homes and nursing homes with frequent opportunities for physical and social activity (Spangler et al, 2019). In addition, as artificial intelligence advances, applying data-driven intelligent platforms has huge potential in health management and health decision-making (Gu et al, 2019), effectively improving organizational performance and internal and external satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…To enhance the institutional satisfaction of hypertension patients within elderly caring SOs, we suggest that elderly caring SOs should improve their environment and service quality while also expanding social capital into the elderly care sector to provide targeted elderly care services. The findings of previous study indicated that nursing home residents are more satisfied in smaller nursing homes and nursing homes with frequent opportunities for physical and social activity (Spangler et al, 2019). In addition, as artificial intelligence advances, applying data-driven intelligent platforms has huge potential in health management and health decision-making (Gu et al, 2019), effectively improving organizational performance and internal and external satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Social care, including nursing homes and in-home care, is provided at the municipal level. Although all nursing homes are publicly financed, approximately 20.5% of nursing homes are run by private actors (Spangler et al, 2019). Due to the largely decentralized character of the health care system governance between the national government and the regions relies on negotiation and collaboration (Fredriksson, 2012).…”
Section: Health Systems' Institutional Backgroundsmentioning
confidence: 99%
“…regulatory compliance) but better on individual quality indicators. (184, 186) Size may also interact with other facility characteristics that may impact on quality e.g. larger hospitals tend to be located in urban areas.…”
Section: Resultsmentioning
confidence: 99%